The ultimate engineer eaudiobook The remarkable life of nasa's visionary leader george m. low. - Jurek, Richard (Outward Odyssey: A People's History of Spaceflight., 2020)
Described as the "ultimate engineer" during his career at NASA, George M. Low was a visionary architect and leader from the agency's inception in 1958 to his retirement in 1976. As chief of manned spaceflight at NASA, Low was instrumental in the Mercury, Gemini, and Apollo programs. Low's pioneering work paved the way for President Kennedy's decision to make a lunar landing NASA's primary goal in the 1960s. After the tragic 1967 Apollo 1 fire that took the lives of three astronauts and almost crippled the program, Low took charge of the redesign of the Apollo spacecraft, and he helped lead the program from disaster and toward the moon. Under Low there were five manned missions, including Apollo 11, the first manned lunar landing. Low's clandestine negotiations with the Soviet Union resulted in a historic joint mission in 1975 that was the precursor to the Shuttle-Mir and International Space Station programs. At the end of his NASA career, Low was one of the leading figures in the development of the space shuttle in the early 1970s, and he was instrumental in NASA's transition into a post-Apollo world. Afterward, he embarked on a distinguished career in higher education as a transformational president of Rensselaer Polytechnic Institute, his alma mater.